NSAIDs Naproxen, Ibuprofen, Salicylate, and Aspirin Inhibit TRPM7 Channels by Cytosolic Acidification - Chokshi, Rikki; Bennett, Orville; Zhelay, Tetyana; Kozak, J. Ashot (Frontiers in Physiology, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are used for relieving pain and inflammation accompanying numerous disease states. The primary therapeutic mechanism of these widely used drugs is the inhibition of cyclooxygenase 1 and 2 (COX1, 2) enzymes that catalyze the conversion of arachidonic acid into prostaglandins. At higher doses, NSAIDs are used for prevention of certain types of cancer and as experimental treatments for Alzheimer’s disease. In the immune system, various NSAIDs have been reported to influence neutrophil function and lymphocyte proliferation, and affect ion channels and cellular calcium homeostasis. Transient receptor potential melastatin 7 (TRPM7) cation channels are highly expressed in T lymphocytes and are inhibited by Mg2+, acidic pH and polyamines. Here we report a novel effect of naproxen, ibuprofen, salicylate and acetylsalicylate on TRPM7: at concentrations of 3 - 30 mM they reversibly inhibited TRPM7 channel currents. By measuring intracellular pH with the ratiometric indicator BCECF, we found that at 300 µM to 30 mM, these NSAIDs reversibly acidified the cytoplasm in a concentration-dependent manner, and propose that TRPM7 channel inhibition is a consequence of cytosolic acidification, rather than direct. NSAID inhibition of TRPM7 channels was slow, voltage-independent and displayed use-dependence, increasing in potency upon repeated drug applications. The extent of channel inhibition by salicylate strongly depended on cellular PI(4,5)P2 levels, as revealed when this phospholipid was depleted with voltage-sensitive lipid phosphatase (VSP). Salicylate inhibited heterologously expressed wildtype TRPM7 channels but not the S1107R variant, which is insensitive to cytosolic pH, Mg2+ and PI(4,5)P2 depletion. NSAID-induced acidification was also observed in Schneider 2 cells from Drosophila, an organism that lacks orthologous COX genes, suggesting that this effect is unrelated to COX enzyme activity. A 24-hour exposure to 300 µM-10 mM naproxen resulted in a concentration-dependent reduction of cell viability. In addition to TRPM7, the described NSAID effect would be expected to apply to other ion channels and transporters sensitive to intracellular pH.